Pengenalan dan Pelatihan Drama Berbahasa Inggris pada Ekstrakurikuler English Club SMP Muhammadiyah 8 Batu - Agista Nidya Wardani; Triastama Wiraatmaja (Program Pendidikan Vokasi Universitas Brawijaya, 2020)
Abstract: Introducing and Coaching English Drama in English Club Extracurricular in SMP Muhammadiyah 8 Batu. SMP Muhammadiyah 8 Batu is one of business enterprises owned by Muhammadiyah located in Batu, East Java. Students in this school have interest and ability in English, but they do not have enough access to sharpen their ability. The reason lies behind it is the lack of extracurricular activity focusing on stimulating their English ability, especially in literature. Literature is an important aspect in language. In this occasion ahead, the focus is on drama. Coaching English drama in extracurricular is expected to facilitate the students. The result of this program was that the coaching clinic was able to help to train and establish the students’ ability in performing English drama. The students were quite enthusiastic in following the program instead of many obstacles found. The obstacles were that not all students had high interest in English drama, the students had lack knowledge of pronunciation, and lack understanding of drama as a whole.